IMPLEMENTASI BUDAYA FLY-HI DI UNIT RESERVASI DAN TICKETING PT GARUDA INDONESIA BRANCH OFFICE YOGYAKARTA - , ADINDA FARRAH YUNIAR, Widyarini Wirjono, S.E., M.M. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Along with the progress of the mindset that the more intelligent people in determining how to meet the needs of an increasingly complex life fosters a competitive attitude for any company. The increasing demand for economic value of a product or service must encourage innovation and the emergence of a whole company now services both business and non-competing services in a good business strategy to survive and make a profit. Garuda Indonesia is one of the flag carrier airline (Flag Carrier) apply one strategy through which corporate culture FLY-HI to create a good quality product and can achieve customer satisfaction which leads to customer loyalty to the product. This study aims to determine the role of culture and contribution to FLY-HI on service improvement PT Garuda Indonesia and how they affect customer satisfaction through qualitative analysis research method with the translation of the source data that has been collected authors in PT Garuda Indonesia Branch Office of Yogyakarta especially in Unit Reservation and ticketing. The corporate culture that applied by personnel of Garuda Indonesia in Reservation and Ticketing unit is a soft structure consisting of the values and behaviors are translated into the main. In addition to support consistency in application of FLY-HI, Branch Office of Yogyakarta also elaborate on added values and conduct training and development so that employees in Unit Reservation and Ticketing can apply the culture better. However, the implementation of FLY-HI, PT Garuda Indonesia Branch Office of Yogyakarta still encountering some resistance.